2010
DOI: 10.1242/jeb.040279
|View full text |Cite
|
Sign up to set email alerts
|

Red junglefowl have individual body odors

Abstract: SUMMARYOlfaction may play an important role in regulating bird behavior, and has been suggested to be involved in feather-pecking. We investigated possible differences in the body odors of red junglefowl females by using an automated olfactometer which assessed the ability of trained mice to discriminate between the odors of uropygial gland secretions (the main carrier of potential individual odors in chickens) of six feather-pecked and six non-pecked birds. All mice were clearly able to discriminate between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Mice have been used in experiments where they were asked to discriminate between odors sampled on birds (Celerier et al, 2011; Karlsson et al, 2010). The conclusion of these studies was that mice can discriminate olfactory and kin signatures in birds.…”
Section: Importance Of Chemosignals In Successive Reproductive Stagesmentioning
confidence: 99%
“…Mice have been used in experiments where they were asked to discriminate between odors sampled on birds (Celerier et al, 2011; Karlsson et al, 2010). The conclusion of these studies was that mice can discriminate olfactory and kin signatures in birds.…”
Section: Importance Of Chemosignals In Successive Reproductive Stagesmentioning
confidence: 99%
“…Volatile compounds, capable of being sensed at a distance, may serve as intraspecific chemical signals. For example, individual odorant signatures have been identified in petrels (Bonadonna et al, 2007), red junglefowl (Karlsson et al, 2010), and dark-eyed juncos (Whittaker et al, 2010). These individual signatures have been associated with mate choice and recognition (Mardon et al, 2010;Whittaker et al, 2010) and with parenting behaviors (Whittaker et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We found that linear and branched carboxylic acids were the predominant volatile compounds in the secretions, and that their signal strengths varied significantly with exogenous testosterone and with photoperiod but that sex had no significant effect. As a result of the experimental design, that study focused exclusively on the most volatile components of the secretion samples, those containing up to six carbon atoms, whereas in other bird species uropygial secretions containing linear alcohols and carboxylic acids with much longer aliphatic chains have been identified (Sandilands et al, 2004;Montalti et al, 2005;Bonadonna et al, 2007;Soini et al, 2007;Karlsson et al, 2010;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This is probably why, despite three decades of physiological and behavioural studies establishing the existence of avian olfactory functions [1], chemical communication has been essentially ignored. Recent research, however, suggests that chemosignals may contribute to avian social behaviours [2][3][4][5][6], thus challenging our understanding of birds' ecology. Petrel seabirds, which possess a developed olfactory system [7], a noticeable musky scent and a life history favourable to olfactory-mediated behaviours [8], are appropriate models to investigate these questions [9].…”
Section: Introductionmentioning
confidence: 99%